Stability of single - layer cube armoured roundheads under wind and swell waves - Yuksel, Yalcin; Cevik, Esin; Sahin, Cihan; van Gent, Marcel R. A.; Rehber, Burak; Polat, Baran; Mustafazade, Chingiz; Inal, Umutcan; Ogur, Mehmet Utku (ELSEVIER, 2026)
This study investigates the stability of single-layer cube-armored breakwater roundheads under varying wave conditions, focusing on the influence of wave steepness, packing density, and cube material density. Experiments were conducted to assess the impact of different packing arrangements (62 % and 69 %) and unit weights (24 kN/m3 and 31.5 kN/m3) on the movement and displacement behavior of armor units. Wind and swell wave conditions were analyzed to evaluate sector-specific behavior across the roundhead. The results reveal that wave steepness plays a critical role in damage initiation, with wind waves causing earlier and more significant movement in the frontal sectors, while swell waves lead to delayed but widespread displacements toward the rear sectors due to enhanced diffraction effects. The roundhead exhibited non-uniform damage distribution, particularly in the second (45 degrees-90 degrees) and third (90 degrees-135 degrees) sectors, which emphasizes the importance of a sector-specific analysis in the design process. Furthermore, this study showed that packing density significantly influences the stability, with higher packing densities providing improved stability, irrespective of the block material density. High density (HD) cubes exhibited less movement compared to normal density cubes, highlighting the importance of geometric arrangement and lateral resistance in ensuring stability. Furthermore, a new formula has been derived based on the experimental data for the one-layer placement of normal density (ND) cubes. Overall, the findings underscore the need for a detailed sector-specific analyses in the design and evaluation of breakwater roundheads to enhance stability and resilience under varying wave conditions.
Keywords: Breakwater roundhead; Cube armour; 3D physical model; Stability number; Damage pattern; Packing density; Engineering